Validation of the Satisfaction with Life Scale and its relationship with the dimensions of self-concept in Peruvian university students - Oliver, Amparo (2018)
Life satisfaction has been the object of several studies, mostly assessed with the Satisfaction with Life Scale (SWLS). Recently, interest has been shown in the relationship between life satisfaction and self-concept, because life satisfaction seems to depend on the cultural context. The purpose of this research was to study the properties of the SWLS in a sample of Peruvian students, and to analyze the relationship between life satisfaction and self-concept in the Peruvian context. The study population consisted of 527 university students from Lima, Peru. Firstly, a confirmatory factor analysis was estimated and assessed, and reliability estimates of the scale and its items were calculated. Subsequently, a MIMIC structural equation model in which self-concept predicted life satisfaction was tested. The results show appropriate psychometric properties of the scale in Peruvian students, and demonstrate the relationship of this construct with the academic, family and physical dimensions of self-concept.